PENERAPAN METODE JIGSAW DALAM PEMBELAJARAN MENULIS TEKS PUISI PADA SISWA KELAS X SEMESTER II SMK NASYRUL ULUM GEGESIK TAHUN PELAJARAN 2022/2023 - Akid, Akid; Sholeh, Muhammad; Subaweh, Ahmad Maskur (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
The study involved X grade students from SMK Nasyrul Ulum Gegesik during the 2022/2023 academic year. The experimental class had 30 students from X TBSM 4, while the control class had 29 students from X TBSM 3. The study aimed to improve students' poetry writing skills in class X at SMK Nasyrul Ulum Gegesik during the 2022/2023 academic year. The research questions focused on the effectiveness of the jigsaw model for teaching poetry writing to X TBSM students and the differences in learning activities using the jigsaw model. The study used a quantitative quasi-experimental design, with data collected through observations and pretest/posttest assessments. The statistical analysis showed that the jigsaw method was effective for teaching poetry writing to X grade students at SMK Nasyrul Ulum Gegesik during the 2022/2023 academic year. The observations also indicated increased student engagement in learning to write poetry texts using the jigsaw method.